(untitled) (Al-Farooq Journal of Sciences, 2026)
Purpose: This study aimed to investigate the impact of Human Resource Management (HRM) practices (training and development, performance appraisal, compensation and incentives, selective recruitment, and employee empowerment) on job performance in public and private sector institutions in the Green Mountain (Jabal al-Akhdar) region of Libya. Methodology: The study adopted a descriptive-analytical approach, utilizing content analysis as the primary research tool, alongside the analysis of official documents, administrative reports, and institutional records available for the targeted organizations during the period from 2020 to 2024. A purposive sample of eight institutions (four governmental and four private) in the cities of Bayda and Shahat was selected. The study employed descriptive analysis (frequencies, percentages, arithmetic means) and comparison between sectors, using qualitative classifications to assess implementation levels and performance. Findings: The results revealed a notable positive impact of HRM practices on job performance. Training and development practices recorded the highest impact, followed by compensation and incentives. The results also revealed a clear disparity between the public and private sectors in favor of the private sector in implementing these practices. The institutions faced severe challenges due to political and legislative instability, which led to weak implementation of some modern practices. Recommendations: The study recommended adopting sustainable HRM strategies, enhancing digital training systems, building continuous feedback-based performance evaluation systems, and reforming labor legislation in line with international labor standards.